Perceptions of poverty in Spain: differences in the attitudinal profiles between women and men - Terol Cantero, M. Carmen; Martin-Aragón Gelabert, Maite; Vázquez Rodríguez, Carolina; Lledó Boyer, Ana; García Soler, Jose Enrique (Frontiers in Psychology, 2023)
Poverty is a multidimensional phenomenon that encompasses privation of education, health or housing. Women show more positive perceptions of poor people, making external attributions for the causes of poverty or the circumstances that explain it. The aim of this study is to analyse perceptions of poverty, identifying the differences in attitudinal profiles between women and men, and the influence of their political and religious beliefs. The sample consists of 278 participants (154 women and 124 men), who completed a sociodemographic questionnaire and the Scale of Attitudes and Stereotypes towards Poverty. The results showed two attitude profiles for women and men, with differences in the first profile, where women or men did not have religious beliefs, had left-wing or centre-left political ideas and favorable attitudes about poverty.